Government Intervention in Employment in Indonesia Based on Welfare State Theory - Rika Jamin Marbun; Lidya Rahmadani Hasibuan (RIRAI Publisher, 2023)
The emergence of the theory of the welfare state provides wider intervention to the state, in this case the government, especially in seeking the welfare of society, including in terms of employment. The Indonesian Constitution affirms philosophically that promoting public welfare is the responsibility of the government so that its role in employment is very much needed. The relationship between workers/laborers and employers arises from existence of a working agreement. The nature of the prevailing work assention is decided by the boss straightforwardly putting the position of the worker/laborer as the frail party. Therefore, even though at first the employment relationship only involved workers/laborers and employers, it needs to be regulated and supervised by the government as a form of protection for workers/laborers who are always in a disadvantageous position. The presence of the government as the maker and implementer and supervisor of employment policies is a form of implementation and development of welfare state concept. This concept emphasizes that the state does not only maintain law and order but is mindful for looking for the welfare of the individuals. The presence of the government as the maker and implementer and supervisor of employment policies is a form of implementation and development of the concept of the Welfare State. This concept emphasizes that the state does not only maintain law and order but is responsible for seeking the welfare of the people. The presence of the government as the maker and implementer and supervisor of employment policies is a form of implementation and development of the concept of the Welfare State. This concept emphasizes that the state does not only maintain law and order but is dependable for looking for the welfare of the people.This welfare state hypothesis was received within the introduction to the 1945 Structure of the Republic of Indonesia. So that inside the scope of work relations it cannot be isolated from the part and destinations of the State.